Cellular and Molecular Mechanisms of Vaccine-induced Protection against Retroviral Infections - Dittmer, U.; Hasenkrug, K.J. (Current Molecular Medicine, 2001)
More than 15 years after the discovery of human immunodeficiency virus (HIV), researchers are still struggling to design a protective AIDS vaccine. A remaining problem is a lack of basic knowledge about the immunological requirements for protection against retroviruses. Infection of macaque monkeys with simian immunodeficiency virus is still the best model for HIV vaccine research. However, in this model it remains difficult to determine protective immunological mechanisms because of limited numbers of experimental animals and their genetic heterogeneity. Thus, fundamental concepts in retroviral immunology have to be defined in other ways such as mouse models. This minireview summarizes new findings on cellular and molecular mechanisms in protection of mice against Friend murine retrovirus infection. It has been shown that complex immune responses, including B and T cell responses, are required for efficient protection in this model. Multiple viral antigens are necessary to elicit such broad immune reactivity. Efficacious vaccines must protect not only against acute disease, but also against the establishment of persistent infections or the host is at serious risk of virus reactivation. The minireview closes with a discussion on the relevance of findings from the mouse model on the design of a protective vaccine against HIV.
Keywords: RETROVIRAL INFECTIONS